Nitrogen deposition cancels out exotic earthworm effects on plant‐feeding nematode communities. (3rd April 2017) - Shao, Yuanhu; Zhang, Weixin; Eisenhauer, Nico; Liu, Tao; Xiong, Yanmei; Liang, Chenfei; Fu, Shenglei
Summary: The activity and spread of exotic earthworms often are spatially correlated with N deposition because both arise from human activities. Exotic earthworms, in turn, can also greatly affect soil abiotic and biotic properties, as well as related ecological processes. Previous studies showed, for example, that earthworms can counteract the detrimental effects of plant‐feeding nematodes on plant growth. However, potential interactive effects of N deposition and exotic earthworms on ecosystems are poorly understood. We explored the changes in density of plant‐feeding nematodes in response to the presence of exotic earthworms, and whether these changes are altered by elevated N deposition in a two‐factorial field mesocosm experiment at the Heshan National Field Research Station of Forest Ecosystem, in southern China. Our results show that earthworm addition marginally significantly increased the density of exotic earthworms and significantly increased the mass of earthworm casts. The total density of plant‐feeding nematodes was not significantly affected by exotic earthworms or N deposition. However, exotic earthworms tended to increase the density of plant‐feeding nematode taxa that are less detrimental to plant growth (r‐strategists), while they significantly reduced the density of more harmful plant‐feeding nematodes (K‐strategists). Importantly, these earthworm effects were restricted to the ambient N deposition treatment, and elevated N deposition cancelled out the earthworm effect. Although exotic earthworms and N deposition interactively altered foliar N : P ratio in the target tree species, this did not result in significant changes in shoot and root biomass in the short term. Overall, our study indicates that N deposition can cancel out exotic earthworm‐induced reductions in the density of harmful plant‐feeding nematodes. These results suggest that anthropogenic N deposition can alter biotic interactions between exotic and native soil organisms with potential implications for ecosystem functioning. Abstract : This study described an important problem in ecology (plant–soil interactions and global change) by assessing how plant‐feeding nematodes respond to the interactive effects of increasing N deposition and exotic earthworm activity. The authors believe that this work can improve our understanding of above‐ground–below‐ground linkages as affected by global change.